Zingiber striolatum phytochemicals ameliorated hyperglycemia symptoms by modulating gut microbial communities in mice with type 2 diabetes mellitus - Liu, Tingting; Ge, Xiaodong; Song, Lu; Wu, Huanhuan; Qian, Xue; Jia, Bowen; Zhao, Chao; Zhuang, Yi (Frontiers in Nutrition, 2025)
IntroductionProlonged hyperglycemia caused by type 2 diabetes mellitus (T2DM) can lead to liver injury and disrupt the community of the gut microbiota that pose significant risks to human health. As a food rich in a variety of active ingredients, Zingiber striolatum (Z. striolatum) exhibits hypoglycemic and hypolipidemic effects. However, the regulatory influence of Z. striolatum ethanol extract (ZSE) on the gut microbiota of T2DM mice or its potential relationship with T2DM pathology remains unexplored.MethodsAfter a one-week acclimation period, 12 mice were randomly selected as the normal group. The remaining 48 mice were employed T2DM model, and then randomly assigned to four groups: the model group, a low-dose ZSE group (ZSE-L, 100 mg/kg/day), a high-dose ZSE group (ZSE-H, 300 mg/kg/day), and a positive control group treated with metformin hydrochloride (MET, 100 mg/kg/day).ResultsAfter a 4-week intervention, the results revealed that ZSE significantly ameliorated fasting blood glucose (FBG), area under the curve of oral glucose tolerance test (AUC of OGTT) and glycated serum protein (GSP) in T2DM mice. Moreover, the high-dose (ZSE-H) treatment increased the relative abundance of beneficial bacteria such as Faecalibaculum, while reducing harmful bacteria such as Bilophila, thereby alleviating insulin resistance. Additionally, ZSE-H demonstrated superior efficacy over low-dose (ZSE-L) in improving FBG, AUC of OGTT, and other hypoglycemic parameters. Predictive analysis of the correlation between gut microbiota and hypoglycemic parameters identified Dubosiella, Bacillus, and Mailhella as potential microbial biomarkers for further investigation into the pathogenesis of T2DM.ConclusionZSE plays a pivotal role in mitigating hyperglycemia in T2DM mice through the modulation of intestinal microbiota communities.